Let us find the solution of the equation "\\frac{d\u00b2y}{dx\u00b2} -y=\\sinh2x". Note that "\\sinh 2x =\\frac{e^{2x}-e^{-2x}}{2}" .
The characteristic equation "k^2-1=0" of the equation "\\frac{d\u00b2y}{dx\u00b2} -y=0" has the solutions "k=1"and "k=-1."
The solution of the equation "\\frac{d\u00b2y}{dx\u00b2} -y=\\frac{e^{2x}-e^{-2x}}{2}" is "y=C_1e^x+C_2e^{-x+}y_p", where "y_p" is a particular solution of "\\frac{d\u00b2y}{dx\u00b2} -y=\\frac{e^{2x}-e^{-2x}}{2}" .
"y_p=Ae^{2x}+Be^{-2x}"
"y_p'=2Ae^{2x}-2Be^{-2x}"
"y_p''=4Ae^{2x}+4Be^{-2x}"
"4Ae^{2x}+4Be^{-2x}-(Ae^{2x}+Be^{-2x})=\\frac{e^{2x}-e^{-2x}}{2}"
"3Ae^{2x}+3Be^{-2x}=\\frac{1}{2}e^{2x}-\\frac{1}{2}e^{-2x}"
"3A=\\frac{1}{2}" and "3B=-\\frac{1}{2}"
"A=\\frac{1}{6}" and "B=-\\frac{1}{6}"
Therefore, the general solution is the following:
"y=C_1e^x+C_2e^{-x}+\\frac{1}{6}e^{2x}-\\frac{1}{6}e^{-2x}=C_1e^x+C_2e^{-x}+\\frac{1}{3}\\sinh 2x"
The particular solution is "y_p=\\frac{1}{3}\\sinh 2x" (for "C_1=C_2=0").
Comments
Leave a comment